MODEL PENGELOLAAN BUDIDAYA KEPITING KULIT LUNAK YANG BERBASIS KELESTARIAN LINGKUNGAN - Muhamad Agus (JURNAL LITBANG PROVINSI JAWA TENGAH, 2010)
The internal problem of pound environment on central of soft shell crab culture in Pemalang Regency has been classified eurytrification (Agus, 2008 ). This research was aimed at geting the model policy in managing the culture of soft shell crab as the manual for fishermer (crab culturer ) who responsibility in sustainable fisheries source. This research was analytical descriptive with the participative resrtospectif methode. The cultur technic that is aplicateed by crab culturer has not been oriented to sustainable environmental yet. It was caused that the policy related with fisheries cultural has not been known by them. FGD results model that based on co management with the some strategies , i.e. capacity building, create the society controller group, increasing the socialitation of related policy with the fisheries and environmental, produced breed crab from breeding unit, open up the comprehensive manufacture industrial that supported by government flexsibel policy in industrial and trading field. Those results brought the implementation of soft shell crab culture oriented to buffer of carrying capacity in out put production in order to keep the environmental more sustain